1990
DOI: 10.1056/nejm199005313222203
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Echocardiographically Determined Left Ventricular Mass in the Framingham Heart Study

Abstract: A pattern of left ventricular hypertrophy evident on the electrocardiogram is a harbinger of morbidity and mortality from cardiovascular disease. Echocardiography permits the noninvasive determination of left ventricular mass and the examination of its role as a precursor of morbidity and mortality. We examined the relation of left ventricular mass to the incidence of cardiovascular disease, mortality from cardiovascular disease, and mortality from all causes in 3220 subjects enrolled in the Framingham Heart S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

64
2,854
5
113

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 5,207 publications
(3,036 citation statements)
references
References 27 publications
64
2,854
5
113
Order By: Relevance
“…In addition, the IVRT/ET and the MPI displayed cardiac dysfunction after multivariable adjustment in all pathological LV geometry groups (Figure 6). These findings of incremental impairment of the cardiac time intervals (especially the IVRT/ET and MPI) with increasing BP and LVMI (Figure 5), and in all types of pathological LV geometry, are important, because a potential future echocardiographic parameter for risk stratification in hypertension should display incremental impairment in the measure with increasing BP and LVMI and in all types of pathological LV geometry, as the risk of ICVD increases continuously with increasing BP5 and LVH 7, 8…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the IVRT/ET and the MPI displayed cardiac dysfunction after multivariable adjustment in all pathological LV geometry groups (Figure 6). These findings of incremental impairment of the cardiac time intervals (especially the IVRT/ET and MPI) with increasing BP and LVMI (Figure 5), and in all types of pathological LV geometry, are important, because a potential future echocardiographic parameter for risk stratification in hypertension should display incremental impairment in the measure with increasing BP and LVMI and in all types of pathological LV geometry, as the risk of ICVD increases continuously with increasing BP5 and LVH 7, 8…”
Section: Discussionmentioning
confidence: 95%
“…Asymptomatic organ damage is an intermediate in the continuum from elevated BP to fulminant ICVD. When asymptomatic organ damage of the heart has occurred, the progression to fulminant ICVD is imminent, explaining the increased risk of ICVD with the observation of asymptomatic organ damage 1, 6, 7, 8. Increased BP and hypertension leads to specific changes in the heart characterized by left ventricular (LV) hypertrophy (LVH) and diastolic dysfunction 1, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…The increased central blood pressures associated with decreased aortic compliance are associated with greater left ventricular mass and concentric remodeling. Greater aortic stiffness, increased left ventricular mass, and concentric left ventricular geometry are all associated with increased risk of future adverse cardiovascular and cerebrovascular events 8, 9, 10, 11, 12, 13. Thus, indexes of altered aortic geometry may be useful for cardiovascular disease (CVD) risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic value of echocardiographic left ventricular (LV) mass1, 2 and its regression with treatment3, 4, 5, 6 are well established. During the past 2 decades, several studies have suggested that the geometric pattern of the left ventricle may improve cardiovascular risk stratification in patients with hypertension 2, 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%